Fenomena “Marriage is Scary” dalam Perspektif Mahasiswi Bercadar di Kota Jember - Nurul Isnaini Batrisyia; Ruston Kumaini; Mukhlishoh Khoirunnisa’; Khoirunnisa Khoirunnisa (Al-Usariyah: Jurnal Hukum Keluarga Islam, 2026)
ABSTRACT The phenomenon "Marriage is Scary" represents the concerns of the younger generation regarding marriage as an institution perceived to be full of challenges and uncertainties. This study aims to examine the perceptions of hijab-wearing female students in Jember City regarding this phenomenon and to explore the factors contributing to their fears and the attitudes they adopt. Using a qualitative approach with a phenomenological method, data were collected through in-depth interviews with seven informants. The results indicate that fear of marriage is still felt despite the informants having strong religious backgrounds. The contributing factors include: 1) fear of losing one's identity, 2) experiences of disharmony in the family, 3) anxiety about choosing a partner, 4) influence of social media, 5) financial instability, 6) differences in religious vision, and 7) unhealthy relationships. In addressing this, they demonstrate selective and planned attitudes, such as: 1) deepening their religious knowledge, 2) self-reflection, 3) seeking social support, 4) emulating the Prophet and their parents, and 5) placing their trust in God. This study shows that fear of marriage is not a form of rejection, but rather a reflection of the awareness and caution of the younger generation in preparing for a household that is strong both emotionally and spiritually. ProKeywords: Marriage is Scary, Concerns, Perceptions, Hijab-wearing students   ABSTRAK   Fenomena "Marriage is Scary" merepresentasikan kekhawatiran generasi muda terhadap pernikahan sebagai institusi yang dianggap penuh tantangan dan ketidakpastian. Penelitian ini bertujuan mengkaji persepsi mahasiswi bercadar di Kota Jember mengenai fenomena tersebut, serta menggali faktor-faktor penyebab ketakutan dan sikap yang mereka ambil. Menggunakan pendekatan kualitatif dengan metode fenomenologi, data diperoleh melalui wawancara mendalam terhadap tujuh informan. Hasil penelitian menunjukkan bahwa ketakutan terhadap pernikahan tetap dirasakan meskipun para informan memiliki latar belakang religius yang kuat. Faktor-faktor pemicunya meliputi: 1) takut kehilangan jati diri, 2) pengalaman keluarga yang tidak harmonis, 3) kecemasan dalam memilih pasangan, 4) pengaruh media sosial, 5) ketidakstabilan finansial, 6) perbedaan visi keagamaan, dan 7) relasi yang tidak sehat. Dalam menyikapinya, mereka menunjukkan sikap selektif dan terencana, seperti; 1) memperdalam ilmu agama, 2) introspeksi diri, 3) mencari dukungan sosial, 4) meneladani sosok Nabi dan orang tua, serta 4) bertawakal kepada Allah. Penelitian ini menunjukkan bahwa ketakutan terhadap pernikahan bukanlah bentuk penolakan, tetapi refleksi dari kesadaran dan kehati-hatian generasi muda dalam mempersiapkan rumah tangga yang kuat secara emosional dan spiritual. Kata kunci: Marriage is Scary, Kekhawatiran, Persepsi, Mahasiswi bercadar